Implementasi Administrasi Fasilitas dan Ketenagakerjaan Laboratorium Bahasa di UIN Raden Mas Said Surakarta - Alfaini, Sania (STAI Auliaurrasyidin Tembilahan, 2022)
Infrastructure is essential to support learning, also an operational standard is needed to optimize the use of infrastructure in accordance with the objectives to be achieved. The purpose of this study was to determine the implementation of facility administration and employment in the language laboratory at UIN Raden Mas Said Surakarta. This research was descriptive qualitative, the data were collected using interviews, observation, and some related documents. The results of the study indicate that the administration of UIN Raden Mas Said already has special requirements in its management, that in the management of facilities and manpower administration it is carried out in accordance with the applicable standards